pt.2 - Atmanand (New Delhi, 1997)
Under the New Economic Policy, the Government of India has initiated measures to tone up the performance of public enterprises at the Central level. The performance of the total public enterprise system is, however, still not satisfactory. It is quite obvious that the state-level public enterprises have been totally neglected by the policy-makers so far as the reformatory measures are concerned. We know that public enterprises in India operate at three levels of administration Central, State and Municipal. The performance of total public enterprises system cannot improve as long as the working of public enterprises is not steramlined. The present book which is the outcome of the author?s research for the doctoral degree, makes an attempt to cover extensively the objectives, growth, investment pattern, financial performane, productivity measurement and managerial problems faced by state-level public enterprises. It is hoped that the present book in two parts will be found immensely useful by the government executives, policy makers, research institutes, management and training institutes, and also the academicians and research scholars and to all those connected with the production, management and development of Public Enterprise is not streamlined.
Keywords: Public sector